Determination of Induction Motor Efficiency Using Non-Linear Programming - Janoušek, Ladislav; Hrabovcová, Valéria (Communications - Scientific letters of the University of Zilina, 1999)
This paper deals with determination of induction motor efficiency, as one of the qualitative indexes of machine operation, by means of acalculation and measurement during its operation. The possibilities of the efficiency calculation are described and it is explained that the simplest method for the efficiency determination is a calculation from a steady state equivalent circuit of the machine. This method is improved by an optimization of the induction machine equivalent circuit parameters based on the measured quantities during steady state operation of the machine. Optimization utilises non-linear programming.